Codeine to Morphine Concentration Ratios in Samples from Living Subjects and Autopsy Cases after Incubation - Berg-Pedersen, Riikka Mari; Ripel, Åse; Karinen, Ritva; Vevelstad, Merete; Bachs, Liliana; Vindenes, Vigdis (Journal of analytical toxicology, 2014)
The codeine to morphine concentration ratio is used in forensic toxicology to assess if codeine has been ingested alone or if morphine and/or heroin have been ingested in addition. In our experience, this interpretation is more difficult in autopsy cases compared with samples from living persons, since high morphine concentrations are observed in cases where only codeine is assumed to have been ingested. We have investigated if codeine and morphine glucuronides are subject to cleavage to the same extent in living and autopsy cases in vitro. We included whole blood samples from eight living subjects and nine forensic autopsy cases, where only codeine ingestion was suspected. All samples were incubated for 2 weeks at 37°C and analyzed for codeine and six codeine metabolites using liquid chromatography tandem mass spectrometry. A reduction in the codeine to morphine concentration ratio was found, both in samples from living subjects (mean 33%, range 22-50%) and autopsy cases (mean 37%, range 13-54%). The increase in the morphine concentrations was greater in the autopsy cases (mean 85%, max 200%) compared with that of the living cases (mean 51%, max 87%). No changes were seen for codeine or codeine-6-glucuronide concentrations. The altered ratios might mislead the forensic toxicologist to suspect morphine or heroin consumption in cases where only codeine has been ingested.